Bioengineering of crop plants for improved tetrahydrofolate production. Issue 1 (1st January 2018) - Chaudhary, Bhupendra; Singh, Nagendra; Pandey, Dhananjay K.
ABSTRACT: De novo synthesis of folates in plants is tightly regulated through feedback-regulation of certain pathway catalysts. Recently, we investigated the prospects of incessant production of folates in an evolutionary conjunction, through the overexpression of feedback targeted and evolutionarily conserved heterologous E.coli dihydroneopterin aldolase ( Ec DHNA) in tobacco. 1 The enhanced production of folates in the transgenic lines was associated with differential allosteric regulatory cavities accessible at Ec DHNA surface having critical amino-acid differences as Ile 64 (His_63), Val 70 (Phe_69), His 75 (Arg_78) and Arg 79 (Glu_72). These structural characteristics are indicative of evolutionary signatures of the catalytic feedback-regulation of folate manufacturing. We exploited the biotechnological potential of such allosterically diverged trans -DHNA for improved folate production in plants. Nonetheless, genetic manipulation of single enzymes modulating complex pathways such as folate biosynthesis is often inadequate to achieve desired phenotypes; therefore, multi-gene integration with explicit genic-combination for folate enrichment in plants has also been projected for future folate agri-biofortification schemes.